Replicability of Japanese Human Resource Management (HRM) approach to Bangladesh: does Culture Matter? - Quddus, S. M. Abdul (Bangladesh Institute of International and Strategic Studies, 2002)
Human Resiurces Management (HRM) practices are the part and parcel of any countries industrial and economic activities. Appropriate and sound technique in managing human resource can be of crucially iimportance in achieving industrial growth even in a resource constraint country. Japan is a good example in this regard. This article, with an overview of the role of HRM in the economy of Japan, analyses the rationals for replication of Japanese HRM approach by drawing theoretical comparison between Japanese management and American management. The relevance of culture in imitating Japanese HRM practices in the context of Bangladesh has also been examined. This examination has led to an argument that substantial convergence or homogenisation of HRM practices around the world not be possible unless managers modify or adapt the mood of implementation of HRM practices to "fit" the cultural values and beliefs.